Synthesis and Characterization of Novel Temperature and pH Responsive Hydroxylpropyl Cellulose-based Graft Copolymers - 李小军 尹明辉 张国亮 张凤宝 (Chinese journal of chemical engineering, 2009)
In this study, double-hydrophilic hydroxylpropyl cellulose （HPC） based copolymers with poly（N- isopropylacrylamide） （PNIPAM） and poly（acrylic acid） （PAA） as graft chains were synthesized and characterized. The release behavior of drug-loaded micelles was studied. The results show that the hydrophilicity of copolymers improves as the pH increases, whereas the hydrophobicity of copolymers enhances as the temperature increases, and all the phase behaviors are reversible. The diameter of micelles decreases and then increases with pH increase. It shows different micellizing behavior under acidic and basic conditions according to the temperature increase. In vitro release experiments, which used theophylline as a model drug, show that the micelles enhance pH sensitivity in the release process.